Justification for the use of Ocimum gratissimum L in herbal medicine and its interaction with disc antibiotics - Nweze Emeka I; Eze Elizabeth E (BMC, 2009)
Abstract Background The ethanolic extract of the leaves of Ocimium gratisimum L. (Lamiaceae), used in traditional medicine for the treatment of several ailments such as urinary tract, wound, skin and gastrointestinal infections, was evaluated for its antibacterial properties against four clinical bacteria isolates namely: Escherichia coli, Proteus mirabilis, Staphylococcus aureus and Pseudomonas aeruginosa and the antifungal properties using a clinical isolate of Candida albicans. A typed bacterium of Escherichia coli ATCC 11775 and another typed fungal strain of Candida albicans (ATCC 90028) were also included. The study also intended to verify if the concomitant administration of conventional antibiotics with Ocimium gratisimum which is normally taken as food (spice) will negatively affect its activity. Methods The agar diffusion method was used to test the in vitro activity of the plant extract. The interaction of the plant extract with some disc antibiotics namely: ciprofloxacin, septrin, streptomycin, ampicillin, nystatin and ketoconazole was tested using the agar overlay inoculum susceptibility disc method. Phytochemical analysis of the extract was performed following established methods. Results The extract showed good but varying in vitro activities against all the isolates tested. While ampicillin showed synergistic interaction with the plant extract against clinical isolates of E. coli and P. mirabilis, septrin was synergistic against the clinical isolate of E. coli only. Similarly, the activity of the extract against C. albicans isolate was synergistic with ketoconazole and nystatin. Conclusion The study has validated the folkloric use of O. gratissimum in traditional medicinal practice and goes further to show that the use of this plant material as food spice may not really threaten the efficacy of some conventional antibiotics that may have been taken concomitantly with it as is the popular belief in the practice of herbal medicine in local/rural communities of many countries in the world.